Reengineering of gear tools on the basis of the unified description of parameters - Пасечник, Виталий Анатольевич; Воронцов, Борис Сергеевич (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2018)
An original approach to the technology of gear reengineering for the conditions of worn gears is presented. The modern hardware and software complexes for creating an electronic standard for gearing are considered. Models of the unified description of gearing invariant to the initial profile of the gearing and original software that implements them are presented. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)